1993
DOI: 10.1111/j.1745-459x.1993.tb00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single Product Scaling and Relative‐to‐reference Scaling in Sensory Evaluation of Dairy Products

Abstract: Single product scaling and relative‐to‐reference scaling were compared on the basis of numbers of significant differences among chocolate milks and among vanilla yogurts using both trained and untrained panels. The study involved 920 comparisons among product means with appearance, flavor and mouthfeel attributes. Although there were a greater number of significant t‐tests when the relative‐to‐reference scales were used by both trained and untrained panels, the differences between scale types were minor. Panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…Larson-Powers and Pangborn (1978) found the deviation-from-reference scale to be more sensitive than an unanchored type of scale since more significant differences were found among the different samples for more descriptors using the deviation-from-reference scale as opposed to the unanchored scale. In contrast to Larson-Powers and Pangborn (1978); Stoer and Lawless (1993), using the same 2 scales used in the earlier study with a balanced design, found that the deviation from reference and the unanchored scale were equally discriminating among samples. The advantages of the self-adjusted scale method are that it deals with the problem of assessor expansiveness, reduces the possibility of scale "end effects," and does not require any significant training, which makes it suitable for consumer testing.…”
Section: S: Sensory and Food Qualitycontrasting
confidence: 67%
“…Larson-Powers and Pangborn (1978) found the deviation-from-reference scale to be more sensitive than an unanchored type of scale since more significant differences were found among the different samples for more descriptors using the deviation-from-reference scale as opposed to the unanchored scale. In contrast to Larson-Powers and Pangborn (1978); Stoer and Lawless (1993), using the same 2 scales used in the earlier study with a balanced design, found that the deviation from reference and the unanchored scale were equally discriminating among samples. The advantages of the self-adjusted scale method are that it deals with the problem of assessor expansiveness, reduces the possibility of scale "end effects," and does not require any significant training, which makes it suitable for consumer testing.…”
Section: S: Sensory and Food Qualitycontrasting
confidence: 67%
“…Sensory Test for Iso-sweetness To find the sucralose concentration that provided sweetness intensity comparable to that of 10% sucrose (iso-sweet), a sensory test format was adapted from the difference-from-control (Meilgaard et al 1999) and the relative-to-reference tests (Stoer and Lawless 1993). The sensory panel had 27 members, 17 men and 10 women; all liked coffee and drank it occasionally, and their average age was 37.…”
Section: Methodsmentioning
confidence: 99%
“…Of course, this comparison remains one of qualitative nature given that these variables are already significant and sometimes have the same level of significance (p-value). This type of comparison has been used in previous studies (Schutz & Cardello, 2001;Stoer & Lawless, 1993). Out of the 780 possible pairwise differences, scales 1, 3, and 4 had a similar number of significant differences with 624, 649, and 630, respectively, with scale 3 obtaining the highest number of differences.…”
Section: Sensitivity Of the Scalesmentioning
confidence: 97%